A közoktatási centralizáció hatása a diákok teljesítményére Magyarországon - Tünde Lénárd (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
– In 2013, an extensive centralization process began in Hungarian public education, transferring all schools previously maintained by municipalities to a central education provider agency. This paper aims to examine the impact of the centralisation process on student performance in Hungary at both primary and secondary levels. Another objective is to separate these effects from those of the vocational school reform, which also took effect in 2013. The analysis uses diff-in-diff and value added models mixed with fixed effects. The results show no detectable effect of centralisation in grades 6 and 8, either in primary school or in 6- or 8-year-long academic secondary school tracks. Even in grade 10, instead of an average centralization effect for the whole period after 2013, we only observe a temporary negative effect of 0.05 standard deviations in 2015 and '17. Based on a model, however, which tries to separate the effects of centralisation and the vocational school reform, it is highly likely that these temporary effects can also be attributed to the negative effects of the reform. The latter reduced the scores of vocational training school students by 0.09-0.16 standard deviations.
Keywords: I21; I28; 330; centralization; institutional changes; student performance